Personal Hygiene and Soil Transmitted Helminth Incidence in Elementary School Students Amanuban Barat District, South Central Timor - Bia, Michael Bhadi; Susilawati, Ni Made; Rantesalu, Agnes; Octrisdey, Karol; Bire, Winioliski L.O. Rohi (JURNAL INFO KESEHATAN, 2022)
Soil-transmitted helminth infection remained a significant public health problem in many developing countries. Elementary school-age children dominated the cases in Indonesia due to poor personal hygiene. South Central Timor had the top three poverty and the highest stunting rates in East Nusa Tenggara. Research to examine the relationship between personal hygiene and the incidence of Soil-Transmitted Helminth infection had never been conducted in South Central Timor. The study population consisted of 279 elementary school students selected from Inpres Nulle Elementary School, Inpres Neonmat Elementary School, and GMIT Nulle Elementary School through the Multistage Random Sampling technique. It was obtained 160 children as the study samples. The study found that 46 children (29.0%) were positive for STH, and 114 (71.0%) were negative for STH. Furthermore, 30 (65.2%) were positive for hookworm, 14 (30.4%) were positive for Ascaris lumbricoides, and 2 (4.4%) children had mixed infections. Multiple Logistic Regression Tests showed a significant effect of washing hands with soap after defecating with p = 0.031 and OR = 7.158. Thus, if a child did not wash his hands with soap after defecating, he had a risk of STH infection by 7.158 times. Furthermore, the effect of eating habits obtained a p = 0.038 and an OR value = 0.133 with the possibility of eating habits that did not protect against STH infection. In addition, the effect of dirty nails obtained a p=0.064 and an OR=5.264, which indicated the risk of contracting STH by 5.264 times. The effect of snacking habit obtained a p = 0.005 and an OR=0.121. It can be concluded that the incidence of STH was simultaneously influenced by the habit of defecating on the ground, washing hands without soap after defecation, eating raw food, having dirty nails, and having poor snacking habits.